2001
DOI: 10.2458/azu_jrm_v54i1_jurado
|View full text |Cite
|
Sign up to set email alerts
|

Effects of biosolids on tobosagrass growth in the Chihuahuan desert

Abstract: Little information is available about seasonal application and carry-over effects of biosolids application to semi-arid grasslands. Biosolids rates of 0 (control), 7, 18, or 34 Mg ha-1 were topically applied to tobosagrass (Hilaria mutica (Buckl.) Benth.) experimental plots in a Chihuahuan desert grassland in western Texas. Biosolids were applied twice in 1994, for one-year-only, either in winter-and-summer (WS), or spring-and-summer (SS) seasons. Half of the plots were irrigated every summer for 4 years (1994… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 11 publications
1
13
0
Order By: Relevance
“…rate in arid grasslands [11]. The lower forage production in New Mexico and Texas can be attributed to low precipitation in their study sites with 267 and 310 mm of mean annual precipitation and lower than average at three out of four years during the study.…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations
“…rate in arid grasslands [11]. The lower forage production in New Mexico and Texas can be attributed to low precipitation in their study sites with 267 and 310 mm of mean annual precipitation and lower than average at three out of four years during the study.…”
Section: Resultsmentioning
confidence: 98%
“…Domestic, aerobic biosolids from the wastewater treatment plant at Aguascalientes city, Mexico, were applied one time only at 0 (control), 15 [20]; total nitrogen (Kjeldahl) [21]; phosphorus (Bray-1) [22]; potassium, calcium, and magnesium, extracted by ammonium acetate; aluminum, zinc, iron, copper, manganese, boron, lead, arsenic, chromium, and cadmium extracted by DTPA [23] and analyzed by Atomic Absorption Spectroscopy; sulfur was extracted with calcium chloride and determined by turbidimetric method and chloride by volumetric methods. Chemical analysis of biosolids (Table 1) showed that pH and electrical conductivity were lower, and organic matter, nitrogen, and phosphorus were slightly higher than values in other studies [10,11]. Because of their N and P contents, biosolids have the potential to improve soil fertility and promote plant growth at different agricultural scenarios.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The beneficial use of biosolids as soil amendment and the enhancement of rangeland plant production have been documented (Fresquez et al 1990;Jurado and Wester 2001;Mata-Gonzá lez et al 2002, 2004. Biosolids, however, require certain quality standards to prevent contamination.…”
Section: Introductionmentioning
confidence: 99%